Finite volume discretisation for the one-dimensional convection diffusion-dissipation equation - ONDAMI, Bienvenu (International Journal of Applied Mathematical Research, 2016)
This paper is devoted to analysis of a finite volume scheme for a one-dimensional convection-diffusion-dissipation equation having application in pollution of water table. We analyse a scheme corresponding to a semi-descretization, also called method of lines. Results of umerical experiments using this approach are reported.